ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT BERDASARKAN JENIS KELAMIN DI SMP NEGERI 15 PALU - Ika Kurniawan Domut; I Nyoman Murdiana; Sukayasa Sukayasa; Baharuddin Paloloang (Universitas Tadulako, 2025)
This study aims to obtain a description of student errors in solving addition and subtraction of integers based on gender in class VIIA of SMP Negeri 15 Palu. This type of research is descriptive research. The subjects of this study were 1 male student and 1 female student with the most errors taken from 26 students from class VII A. This research was conducted in the even semester of the 2023/2024 academic year. The data of this research were collected by means of tests and interviews. The analysis in this study used Newman's stages. The data analysis techniques in this study were data condensation, data presentation, and drawing conclusions. The results of the study showed that: (1) Male students made transformation errors, process skill errors and errors in writing the final answer. (2) Female students made errors in reading questions, transformation errors, process skill errors and errors in writing the final answers